2020
DOI: 10.3390/s20061569
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Magnetic Field Sensors for Biomedical Applications

Abstract: The development of magnetic field sensors for biomedical applications primarily focuses on equivalent magnetic noise reduction or overall design improvement in order to make them smaller and cheaper while keeping the required values of a limit of detection. One of the cutting-edge topics today is the use of magnetic field sensors for applications such as magnetocardiography, magnetotomography, magnetomyography, magnetoneurography, or their application in point-of-care devices. This introductory review focuses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(102 citation statements)
references
References 243 publications
(308 reference statements)
0
88
0
Order By: Relevance
“…In one hand, it is essential to pursue new piezomagnetic and piezoelectric materials for achieving higher magnetostrictive and piezoelectric coefficients [ 111 ]. In this context, [ 112 ] it was shown that the introduction of CaZrO3 increased electric field–induced strain behavior and stated that, nowadays it is possible to achieve high piezoelectric coefficient d 33 over 400 pC/N even in non-textured KNN ceramics, although there still persist some serious challenges for large-scale applications. It was also suggested the creation of a real MPB as in PZT system to solve the reasonably large temperature dependence of piezoelectric properties of KNN-based ceramics, which is full of scientific interest and technical importance.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…In one hand, it is essential to pursue new piezomagnetic and piezoelectric materials for achieving higher magnetostrictive and piezoelectric coefficients [ 111 ]. In this context, [ 112 ] it was shown that the introduction of CaZrO3 increased electric field–induced strain behavior and stated that, nowadays it is possible to achieve high piezoelectric coefficient d 33 over 400 pC/N even in non-textured KNN ceramics, although there still persist some serious challenges for large-scale applications. It was also suggested the creation of a real MPB as in PZT system to solve the reasonably large temperature dependence of piezoelectric properties of KNN-based ceramics, which is full of scientific interest and technical importance.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…With respect to applications of ME sensors in real-world environments, it is often concluded that the magnetic field sensitivity is harmed by contamination of the ME signals by external vibration noise sources and that, therefore, the decrease or even the elimination of the external noise is an essential challenge for the ME sensors [ 112 ]. The encapsulation of the materials and the use of resonant frequencies outside the contamination noise range are directions that should be followed.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in recent years, the establishment of body-electric interfaces has attracted notable attention via multifarious electronic skins for capturing indexed in big data analytics [ 6 , 7 , 8 , 9 , 10 ]. Some devices can detect toxic agents in the environment and define the quality of the food, and some devices can reflect the human body movement state and physiological information [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. For example, sensors for gustation recognition are immersed in the measured solution, and the changes of the electrical signal can recognize the flavor [ 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The wire-core sensor has high spatial resolution, and it is therefore convenient for measurements of small field sources such as microbeads [4,5].…”
mentioning
confidence: 99%